(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Neurofibroma is a benign tumor of nerve sheath of peripheral nervous system. It frequently involves the skin and rarely the oral mucosa. The pattern of the disease has been recognized as hereditary with an autosomal dominant trait with variable penetrance. The most common variant is neurofibromatosis type I (NF-I). The oral lesions occur as discrete, nonulcerated nodules, which tend to be of the same color as the surrounding mucosa. Usually occurs on the buccal mucosa, palate, alveolar mucosa, vestibule and the tongue. A case of asymptomatic swelling of the right side of the tongue near the tip since 02 years is presented. The swelling was gradual in onset and slowly increased in size. It was a solitary diffuse, smooth, firm and non-tender swelling of the right side of the tongue near the tip. Excision was done under lingual nerve block by local anesthetics (2% Lidocain with Adrenalin) and biopsy was performed and histological examination revealed spindle cells having serpentine nuclei, arranged in bundle and fascicles is a fibrillary background. Bangladesh J Otorhinolaryngology 2025; 31 (1) Page-42-46